The Rhetorical Style Structure of the Personal Letter Genre: Contemporary English, Spanish, and Middle Ages Style Structures Compared - Gamboa Mena, Roy (2020)
A look at rhetoric from a stylistic standpoint allows building understanding of current rhetorical practices as evolved forms of rhetoric. By following a qualitative research design described as content analysis by Leedy and Ormrod (2001), the present study describes the style structure differences and similarities in contemporary personal letter writing in English and Spanish as compared to the style structure of letter writing in the middle ages. It was concluded that personal letter writing in both English and Spanish does not fully comply with the style structure cannon of letter writing established for each class. Also, English and Spanish contemporary personal letter writing are rather similar, and the style structure cannons for contemporary personal letter writing in both English and Spanish can be traced back to that of the Middle Ages.